Gbp3 is associated with the progression of lupus nephritis by regulating cell proliferation, inflammation and pyroptosis - Zhongfeng Zhang; Wenyu Song; Run Yan (Taylor & Francis Group, 2023)
Lupus nephritis (LN) is a major cause death in patients with systemic lupus erythematosus. We aimed to find the differentially expressed genes (DEGs) in LN and confirm the regulatory mechanism on LN. The mouse model of LN was constructed by subcutaneous injection of pristane. RNA-seq screened 392 up-regulated and 447 down-regulated DEGs in LN mouse model, and KEGG analysis found that the top 20 DEGs were enriched in arachidonic acid metabolism, tryptophan metabolism, etc. The hub genes, Kynu, Spidr, Gbp3, Cbr1, Cyp4b1, and Cndp2 were identified, in which Gbp3 was selected for following study. Afterwards, the function of Gbp3 on the proliferation, inflammation, and pyroptosis of LN was verified by CCK-8, ELISA, and WB in vitro. The results demonstrated that si-Gbp3 promoted cell proliferation and inhibited the levels of inflammatory factors (IL-1β, TNF-α and IL-8) and pyroptosis-related proteins (GSDMD, Caspase-1 and NLRP3) in a cell model of LN. In constrast, Gbp3 overexpression played an opposite role. In summary, Gbp3 promoted the progression of LN via inhibiting cell proliferation and facilitating inflammation and pyroptosis.